До питання генезису приватного права - Зелена, І.В. (Альманах права, 2012)
У статті розглянуто та охарактеризовано процеси виникнення та розвитку приватного права як правового явища, висвітлено особливості приватного права на різних етапах розвитку суспільства, починаючи від давніх часів та закінчуючи сьогоденням. Розкрито поняття приватного права через призму концепцій сучасного праворозуміння. Зосереджено увагу на первинності приватних відносин щодо публічних та зроблена спроба авторського визначення поняття приватного права. В статье рассматриваются и характеризуются процессы возникновения и развития частного права как правового явления, освещены особенности частного права на различных этапах развития общества, начиная от давних времен и заканчивая современностью. Раскрыто понятие частного права сквозь призму концепций современного правопонимания. Сосредоточено внимание на первичности частных отношений относительно публичных и сделана попытка авторского определения понятия частного права. The article deals with the origin and development of private law as a legal phenomenon. Primary mentioned private law are reflected in the works thinkers of ancient times. The first one is of Tit Libya, and in fact private standards already exist, according to researchers and state law, the Laws of Manu and Laws Hammurabi. For example, the Laws of Manu called eight possible ways of ownership: inheritance, gift, purchase, conquest, usury, performance work, receiving alms, and possession of prescription. At the same time interesting is the fact rather more elaborated binding relationship and consequences that come once in their violation. During the Middle Ages more broadly defines and reveals the private law, focusing on privately owned entity and
its protection. An important step in the history of private law was, in particular, creation a Civil Code of France, better known as the Code Napoleon which were reflected and improved gains in private legal relationships and responsibilities and so called, the German Civil Code, which defines a number of provisions related to private law
and liability. The law of the Soviet period has imperative nature, was an aspect of state policy ensured party government, which was conditioned by the existing form State and legal regime. Herewith abstains the full expression, there was penetration of the state in all spheres of social life, the dissolution of private law as such a right in public. Inherent
for this period is thought of the Ukrainian lawyer that time, Doctor of Public Law, M. Chizhov, that foundation is a private law not individual and public interests. When the state is taking care of all, it takes care both itself, in which case the individual and his private law is a means to achieve values useful for the whole community. Modern views of private law based on the growth of social and personal values such as rights, promote democracy and human rights and citizens. A characteristic feature of modern legal science understanding private law is pluralism, which results in separation of different methodological approaches. In this private right of way is treated as a set of
rules governing social relations in the private interest; higher area, represented by system-ordered unity areas of law based on the complexity of regulation, the industry right from their own features of the subject and method, identical to the concept of civil law, private law property rights, which is different in some areas of law. Thus, the process of becoming private and private law originates since ancient times and continues to the present. Embryos private law is in ancient sources and is characterized by certain primitive and imperfect, however, this again confirms the idea of primacy of private relations of the public. During the Middle Ages more broadly defines and
reveals the possibility of private law focusing on individual private property and its protection. The law of the Soviet period, on the contrary, denies the existence of private law, regulation bringing almost all areas social life at the state level. Modern views of private law based on increasing social and personal values such as law and strengthening democratic principles and human and civil rights.